2006
DOI: 10.1093/annonc/mdl086
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic haematopoietic stem cell transplantation for metastatic renal carcinoma in Europe

Abstract: Patients with metastatic RCC, less than three metastatic locations and a Karnofsky score >70% can be considered for HSCT. Posttransplant DLI and limited chronic GVHD improved the patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
64
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 35 publications
2
64
0
1
Order By: Relevance
“…3,5,7 Addressing a strategy to control disease early after allogeneic HSCT might improve the survival of the patients with RCC. Haploidentical-SCT (haplo-SCT) could provide an enhanced allogeneic T-cell and natural killer (NK)-cell response and augment GVT effect due to the MHC molecule disparity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,5,7 Addressing a strategy to control disease early after allogeneic HSCT might improve the survival of the patients with RCC. Haploidentical-SCT (haplo-SCT) could provide an enhanced allogeneic T-cell and natural killer (NK)-cell response and augment GVT effect due to the MHC molecule disparity.…”
Section: Introductionmentioning
confidence: 99%
“…In a European study, OS was found to be 30% at 2 years after HSCT. 3 However, CALGB data did not support these observations and did not report any objective responses after allogeneic HSCT in patients with advanced RCC. 6 Finally, in a recent report, Bregni and co-workers 7 observed a 5-year survival rate for 20% of 25 patients with metastatic RCC who had reduced intensity conditioning for allogeneic HSCT from HLA-compatible sibling donors.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…2 After anecdotal reports in breast and lung cancer, Childs et al 3 reported in 2000 a consistent GVT effect of allogeneic stem cell transplant against renal cell cancer. GVT effect was then investigated in other tumors: As STWP of the EBMT, we completed several studies of allografting in selected solid tumors, namely renal cell cancer, 4 ovarian cancer, 5 breast cancer, 6 colorectal cancer 7 and others, with circumstantial evidence of GVT in some tumors and occurrence of transplant-related toxicities, mostly GvHD. In renal cell cancer, we have shown a long-term survival effect in a fraction (20%) of patients.…”
mentioning
confidence: 99%
“…In 2008 we initiated an IRB-approved prospective, single-arm phase II study (nicknamed AlloTOR), which combines a reduced-intensity conditioning, HLA-identical sibling donor allograft with post transplant temsirolimus for patients with advanced renal cell carcinoma (RCC) who have failed a thyrosine kinase inhibitor-based therapy. The clinical rationale of this approach relies on the long-term results of allograft in metastatic RCC, [2][3][4] and on the encouraging results of second-or third-line temsirolimus in patients resistant/ refractory to thyrosine kinase inhibitor therapy. 5 In addition, data suggest that rapamycin and related agents relatively increase Tregs and may be beneficial to the protection of the host without compromising the antitumor activity of the transplant.…”
mentioning
confidence: 99%